The effect of social learning on avoidance of aposematic prey in juvenile great tits (Parus major) - Landová, Eva; Hotová Svádová, Kateřina; Fuchs, Roman; Štys, Pavel; Exnerová, Alice (Animal cognition, 2017)
Social learning plays an important role in acquiring new foraging skills and food preferences in many bird species but its potential role in learning to avoid aposematic prey has never been studied. We tested the effect of social learning on the acquisition of avoidance of aposematic insect prey (firebug Pyrrhocoris apterus; Heteroptera) in juvenile, hand-reared great tits (Parus major). Behaviour towards aposematic prey was compared between two groups of birds: (1) the observers that were, prior to encounter with firebugs, allowed to watch the experienced conspecific demonstrator repeatedly refuse to attack the prey, and (2) the control birds that lacked this opportunity. Observing an experienced demonstrator was not sufficient for learning complete avoidance, because birds from both groups attacked at least the first firebug they had encountered in avoidance training. However, the opportunity to observe the avoidance behaviour of another bird significantly increased the rate of subsequent individual learning of observers in comparison with control birds. Social learning also decreased mortality of firebugs killed by the birds during the avoidance learning. Socially enhanced learning to avoid aposematic prey might be a mechanism important especially for naive juvenile birds learning from their parents, but it could also enhance learning in adults from their more experienced flock mates. Because social learning of avoidance may also lead to decreased mortality of aposematic prey, its effect should be taken into account in scenarios considering evolution and maintenance of prey warning signals.
Keywords: Pyrrhocoris apterus; Predatory Behavior; Aposematic prey; predátorské chování; Female; Parus major; sociální učení; Avoidance Learning; zvířata; učení vyhýbat se; Social Learning; ženské pohlaví; Male; Social learning; Heteroptera; Naive predators; Passeriformes; Animals; mužské pohlaví; Warning signalling; Avoidance learning